The Impact of Aerobic Activity Programs on Quality of Life and Cardiovascular Fitness in the Elderly: A Review - Agung Wahyu Permadi; Tanjung Subrata (WMJ (Warmadewa Medical Journal), 2025)
Aerobic activity is a gradual and targeted activity designed to enhance the body's ability to utilize cardiac and respiratory capacity (oxygen) effectively in the elderly. The growing number of elderly people and their long-term effects on psychological factors affecting their quality of life. This review aims to evaluate and synthesize scientific evidence on the effects of aerobic activity programs on quality of life and cardiovascular fitness in the elderly. This analysis uses the Preferred Reporting for Systematic Review and Meta-analysis (PRISMA) method. A systematic search was conducted by searching the Cochrane Database of Systematic Reviews, Embase, and Pubmed, independently using the terms "Aerobic", "Elderly", "Cardiovascular fitness", "Prevention", "Quality of life", "QoL", "exercise", "training", "sports", and "Physical". A total of 11 studies were included, demonstrating that engagement in aerobic physical activity leads to significant improvements in various health parameters among the elderly. These enhancements encompass cardiovascular health, physical function, and emotional well-being. A moderate, measured aerobic exercise program integrated into a daily routine can greatly benefit the health and vitality of the elderly. Such activities improve cardiovascular health, enhance physical function, and boost mental and emotional well-being, contributing to a better quality of life as we age.